2016
DOI: 10.1111/cmi.12676
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally controlled bacterial vesicle-mediated export

Abstract: Summary Over the past two decades, researchers studying both microbial and host cell communities have gained an appreciation for the ability of bacteria to produce, regulate, and functionally utilize outer membrane vesicles (OMVs) as a means to survive and interact with their cellular and acellular environments. Common ground has emerged, as it appears that vesicle production is an environmentally-controlled and specific secretion process, however it has been challenging to discover the principles that govern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
139
1
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(160 citation statements)
references
References 111 publications
7
139
1
13
Order By: Relevance
“…Vesicles produced by many Gram-negative pathogens, including P. aeruginosa, can elicit host immune responses, and many also serve as delivery mechanisms for bacterial virulence factors 16 . Of particular importance to our studies, OMVs have been implicated in the process of biofilm formation 6,15,17 . Schooling et al demonstrated that OMVs are present in P. aeruginosa biofilm matrix and that bacteria in biofilms exhibit higher OMV production rates as compared to planktonic cells 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vesicles produced by many Gram-negative pathogens, including P. aeruginosa, can elicit host immune responses, and many also serve as delivery mechanisms for bacterial virulence factors 16 . Of particular importance to our studies, OMVs have been implicated in the process of biofilm formation 6,15,17 . Schooling et al demonstrated that OMVs are present in P. aeruginosa biofilm matrix and that bacteria in biofilms exhibit higher OMV production rates as compared to planktonic cells 18 .…”
Section: Introductionmentioning
confidence: 99%
“…OMVs are formed from the envelope of Gram-negative bacteria and are small, discrete extracellular structures containing distinct membrane protein, lipid, and soluble periplasmic content 15 . They are known to interact with the external environment, including host tissues 16 .…”
Section: Introductionmentioning
confidence: 99%
“…OMVs are proteo-liposomes of 10-200 nm diameter formed by budding of the outer membrane, and can contain membrane-associated and soluble proteins, nucleic acids and small molecules. OMV production is a constitutive process, but is also a protective response and increases in the presence of environmental stresses and during infection (24-27). Often, this increase in OMV production is co-regulated with other virulence mechanisms (24, 28).…”
Section: Introductionmentioning
confidence: 99%
“…Phospholipid accumulation in the OM triggers the formation of these spherical structures, which are composed of a membrane bilayer derived from the bacterial OM (6). The amount of OMVs produced by a given bacterium varies in response to environmental conditions like growth phase, nutrient sources, iron and oxygen availability, abiotic stress, presence of host cells, and during biofilm formation (7). Depending on the species and growth conditions, OMVs may enclose cytoplasmic, periplasmic and transport proteins, as well as DNA, RNA, and outer membrane-derived components such as LPS and phospholipids.…”
Section: Introductionmentioning
confidence: 99%